Comparative analysis of grain productivity and biometric elements of winter wheat varieties depending on the variety change periods - O. V. Levakova; O. V. Gladysheva; M. I. Kostanyants (Зерновое хозяйство России, 2023)
The current study was carried out at the Institute of Seed production and Agrotechnologies, Branch of the Federal Budgetary Scientific Institution “Federal Research Agro-Engineering Center VIM” (Ryazan region) on dark gray forest soil of medium fertility (organic matter content 5.60 %) in 2018–2022. The objects of the study were 9 winter common wheat varieties (developed by the FSBSI FRC “Nemchinovka” and FSBSI FRAC VIM), which were included in the State List of Breeding Achievements from 2005–2023 in the Central region of the Non-Blackearth part of the Russian Federation and divided according to the variety change periods, i.e. period V with ‘Galina’, ‘Angelina’, ‘Moskovskaya 56’, ‘Viola’; period VI with ‘Danaya’, ‘Felitsiya’, ‘Galateya’, ‘Anfisa’, ‘Boyarka’. The purpose of the study was to analyze the grain yield and biometric elements of its structural indicators in the winter common wheat varieties, depending on the variety change periods in the conditions of the southern part of the Central region of the Russian Federation. During the study, there has been established an excess of the average (by 15.9 %), minimum (by 27.9 %) and maximum (by 8.3 %) productivity of varieties of the last variety change period with 5.2 % advantage in realizing the yield potential (average 74.5 %) and adaptability coefficient by 17.4 % (average value over 1.0). The variety ‘Galateya’ has high values of productivity potential with adaptability coefficient of 1.12. There has been established that in modern varieties there was a decrease in the stem length by 5.9 cm on average. The shortest varieties were ‘Viola’, ‘Felitsiya’, ‘Anfisa’ and ‘Boyarka’ with 96–97 cm. There has been established that the varieties of the period VI experienced a stem augmentation on 12.7 %, number of grains per head on 2.5 %, grain weight per head on 11.7 % and 1000-grain weight on 4.2 % in comparison with the varieties of the previous selection. A significant contribution to the productivity of new varieties (r ≥ +0.700) was made by the traits ‘number of grains per head’ and ‘grain weight per head’. The variety ‘Anfisa’ had the longest head of 11.3 cm. The varieties ‘Galateya’, ‘Felitsiya’, and ‘Boyarka’ had number of grains per head more than 42.0 pcs., and grain weight per head of more than 2.0 g. All varieties of the last variety change had large grain, m1000 > 46.0 g, the variety ‘Galateya’ had especially coarse grain of 49.1 g.